1998
DOI: 10.1002/(sici)1097-0282(1998)48:2<101::aid-bip2>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Folding of branched RNA species

Abstract: The global structures of branched RNA species are important to their function. Branched RNA species are defined as molecules in which double‐helical segments are interrupted by abrupt discontinuities. These include helical junctions of different orders, and base bulges and loops. Common helical junctions are three‐ and four‐way junctions, often interrupted by mispairs or additional nucleotides. There are many interesting examples of functional RNA junctions, including the hammerhead and hairpin ribozymes, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 109 publications
(94 reference statements)
0
29
0
Order By: Relevance
“…Although these base pairs are not directly involved in tertiary interactions in the crystal structure (Serganov et al 2004), they could be involved in the global architecture of the aptamer given their close proximity to the junction. Indeed, the global architecture of RNA junctions has been shown to be influenced by proximal base pairs by means of coaxial stacking (Lilley 1998). However, native gel and RNAse T1 assays performed on the aptamer variant C45G-G43C revealed that the looploop interaction can take place, suggesting that this mutation does not significantly perturb the loop-loop interaction (data not shown).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although these base pairs are not directly involved in tertiary interactions in the crystal structure (Serganov et al 2004), they could be involved in the global architecture of the aptamer given their close proximity to the junction. Indeed, the global architecture of RNA junctions has been shown to be influenced by proximal base pairs by means of coaxial stacking (Lilley 1998). However, native gel and RNAse T1 assays performed on the aptamer variant C45G-G43C revealed that the looploop interaction can take place, suggesting that this mutation does not significantly perturb the loop-loop interaction (data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, we sought for evidences relating weak 2AP affinity and severe disruption of the loop-loop interaction by using a native gel electrophoresis assay. This technique can be used to study global conformational changes in nucleic acids whereby a compact structure generally migrates faster than a more extended one (Lilley 1998;Yamauchi et al 2005). We reasoned that aptamers having a functional loop-loop interaction should have a compact structure when compared to variants compromised in the interaction, and should therefore display a faster migration rate.…”
Section: Effect Of Position 15 On Ligand Bindingmentioning
confidence: 99%
“…There are N linker (joining) sequences for N helices in a junction loop, although some of the linker sequences may be of zero length. Although junction loops have not been as systematically or extensively studied as the simpler hairpin and internal loops, some generalizations have been made for the more common three-way and four-way junctions (Lilley, 1998(Lilley, , 2000. Common examples of junction loops are those in tRNA and the hammerhead ribozyme.…”
Section: Junction Loops/multiloopsmentioning
confidence: 99%
“…Like protein enzymes, they must fold into a conformation that provides a local environment in which catalysis can proceed. Branched helical junctions are very common in RNA and frequently are essential for their function (2), but the dynamic mechanisms by which the junctions contribute to RNA folding are not well understood.…”
mentioning
confidence: 99%